Influence of pre-endoscopic duration of esophageal food impaction on endoscopy time and postprocedure adverse events - DiLeo, Daniel Anthony; Zenger, Cameron; Quarta, Giulio (Frontiers in Gastroenterology, 2022)
Objectives Esophageal food bolus impaction is a medical emergency and 10-20% of impacted food boluses will require endoscopic removal. Emergent and prolonged procedures are associated with increased adverse events. We are interested in the relationship between the pre-endoscopic duration of esophageal food impaction and the duration of esophagogastroduodenoscopy (EGD) performed to remove the impacted food bolus. Methods Between 2010 and 2021, we examined EGD procedures performed for esophageal food impaction. Subjects were classified according to pre-endoscopic duration of food impaction. Results We found a positive correlation between pre-endoscopic duration of food impaction and procedure length (r=0.18). Esophageal impactions with mixed foods resulted in the longest procedure duration (p<0.05). Increasing age, male gender, and duration of impaction greater than 42 hours were significantly associated with increased procedure duration (p<0.05). Esophageal perforations, prolonged intubations, admissions following EGD, and readmissions were associated with EGD duration greater than 25.5 minutes. No adverse events occurred in patients who underwent EGD within 6 hours of symptom onset. Conclusions In the case of an esophageal food impaction, the time between symptom onset and endoscopy is positively correlated with procedure length and risk of adverse outcomes. We suggest that food impaction should remain an indication for emergent endoscopy. Prospective studies evaluating the safety and outcomes of prolonged time to endoscopy will further clarify the management of esophageal food impactions.